INTEGRASI NILAI KEISLAMAN DALAM MANAJEMEN STRATEGIK UNTUK MEMBANGUN KEUNGGULAN KOMPETITIF LEMBAGA PENDIDIKAN ISLAM DI ERA GLOBALISASI DIGITAL - JABBAR, MOCH. RIKZA ALKHUBRA ABDUL; CHOTIMAH, CHUSNUL; SULISTYORINI, SULISTYORINI (CENDEKIA: Jurnal Ilmu Pengetahuan, 2025)
Islamic educational institutions face the challenges of digital globalization, which have the potential to erode Islamic identity if not supported by strategic management rooted in Islamic values. This study aims to analyze the impact of integrating Islamic values into management strategies to enhance the excellence of Islamic educational institutions in the digital globalization era. This research employs a library research method with a descriptive qualitative approach, analyzing literature related to the integration of Islamic values, strategic management, and the competitive advantage of Islamic educational institutions. The findings indicate that applying values such as trustworthiness (amanah), justice (adil), excellence (ihsan), honesty (shiddiq), and cooperation (ta’awun) not only strengthens the institutions’ Islamic identity but also enhances their adaptability to modernization challenges through innovations based on Islamic technology. This study provides theoretical contributions to the literature on Islamic educational management and practical contributions in the form of strategic guidelines for Islamic educational institutions to maintain their relevance and competitiveness in the digital era. It is expected to serve as a foundation for further development in managing Islamic education oriented towards Islamic values and technological innovation. ABSTRAKLembaga pendidikan Islam menghadapi tantangan globalisasi digital yang berpotensi mengikis identitas keislaman jika tidak didukung oleh manajemen strategik berbasis nilai- nilai Islam. Penelitian ini bertujuan untuk menganalisis pengaruh integrasi nilai keislaman dalam strategi manajemen guna membentuk keunggulan lembaga pendidikan Islam di era globalisasi digital. Penelitian ini menggunakan metode studi kepustakaan dengan pendekatan deskriptif kualitatif, yang menganalisis literatur terkait integrasi nilai keislaman, manajemen strategik, dan keunggulan kompetitif lembaga pendidikan Islam. Hasil penelitian menunjukkan bahwa penerapan nilai-nilai seperti amanah, adil, ihsan, shiddiq, dan ta’awun tidak hanya memperkuat identitas keislaman lembaga tetapi juga meningkatkan adaptabilitas terhadap tantangan modernisasi melalui inovasi berbasis teknologi Islami. Penelitian ini memberikan kontribusi teoretis dalam memperkaya literatur manajemen pendidikan Islam serta kontribusi praktis berupa panduan strategis bagi lembaga pendidikan Islam untuk mempertahankan relevansi dan daya saing di era digital. Penelitian ini diharapkan menjadi dasar untuk pengembangan lebih lanjut terkait pengelolaan pendidikan Islam yang berorientasi pada nilai keislaman dan inovasi teknologi